2023
DOI: 10.1111/apa.16779
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude, fragility and strength: Perspectives of adults born preterm about prematurity

Abstract: Aim The aim of the study was to explore how young adults thought that being born preterm had affected their lives. Methods Adult participants of a research cohort were questioned about their perspectives. Answers were analysed using mixed methods. Results Forty‐five participants evaluated their health at median score of 8/10. When asked about the meaning of being born preterm, 65% had positive self‐centred answers, invoking two main themes: being stronger/‘a fighter’/more resilient and being a survivor/chosen;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Adults born EPT rated their own health as an eight out of a tenpointed scale, even though 78 % of the group had at least one adverse health outcome [41]. The authors concluded that how the "story" of being born EPT was told by the parents is often how the EPT adult internalizes it.…”
Section: Discussionmentioning
confidence: 99%
“…Adults born EPT rated their own health as an eight out of a tenpointed scale, even though 78 % of the group had at least one adverse health outcome [41]. The authors concluded that how the "story" of being born EPT was told by the parents is often how the EPT adult internalizes it.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been several studies that have examined the quality of life of premature infants, [48][49][50][51] only three previous qualitative studies were conducted involving this particular stakeholder group. [52][53][54] The significant strength of this study is that it was the first to investigate the attitudes of adults born prematurely regarding periviability guidelines and personalisation at the limit of viability.…”
Section: Strengths and Limitationsmentioning
confidence: 99%